On the Illusions of the New Media - Balčytienė, Auksė (Sociologija. Mintis ir veiksmas, 2000)
The aim of the article is discuss the duality of the new media. The author critically assesses the view of the new media as empowering and liberating. The author suggests that such a view is grounded on a notion of reflexivity that is abstracted from capabilities of cognition and builds her argument on the studies of human action to understand the difficulties of interpreting the interactive information.
Keywords: new media; interactivity; postmodernism; experiential cognition; reflexive cognition